Versatile OPiv-Supported Organozinc Reagents for Transition-Metal-Catalyzed Cross-Couplings - Liu, Xingchen; Wang, Jixin; Li, Jie (Synlett, 2022)
As one of the most important indispensable tools, organozinc-reagents-based Negishi cross-couplings have been extensively utilized for the synthesis of biologically active molecules and feedstock commodity chemicals. However, the use of air- and moisture-sensitive organozinc halides and expensive palladium catalysis still remain drawbacks. Recently, user-friendly solid OPiv-supported C–Zn, Si–Zn reagents with enhanced air and moisture stability have been prepared, which displayed superior reactivity in various transition-metal-catalyzed cross-couplings, especially in the earth-abundance cobalt and nickel catalysis. Herein, we summarized the recent advances and our research work in the field of the preparation and application of solid organozinc pivalates in the present short review.1 Introduction2 Development of Organozinc Pivalates in Two-Component Cross-Couplings3 Development of Organozinc Pivalates in Three-Component Cross-Couplings4 Conclusion and Outlook
Keywords: organozinc pivalates; silylzinc pivalates; Negishi coupling; alkene difunctionalization; homogeneous catalysis